Machiavellianism and spiritual intelligence as predictors of waste-prevention behaviours among Malaysian university students - Karbalaei, Samaneh; Abdollahi, Abbas; Abdullah, Sabrina J. Ho (Universiti Putra Malaysia Press, 2015)
Understanding the psychological factors related to waste-prevention behaviours of university students could enable local governments and policy makers to craft effective policies to reduce waste. This study utilised a questionnaire-based survey to assess the associations between spiritual intelligence and Machiavellianism as factors that influence waste-prevention behaviours. A total of 210 participants from Universiti Putra Malaysia completed the questionnaires, including the demographic questions, spiritual intelligence inventory, Mach IV, and the waste-prevention behaviours. The data were analysed using Structural Equation Modelling (SEM). The results showed that individuals with higher spiritual intelligence and lower Machiavellianism were more likely to report a positive attitude towards waste-prevention behaviours, and that an inverse association existed between spiritual intelligence and Machiavellianism. Overall, these variables explained 12.0% of the variance in waste-prevention behaviours. Therefore, these findings reinforce the importance of personality traits and cognitive abilities in waste-prevention behaviours.